The Future of Coexistence in the EU and Centripetal Forces, Constitutional Courts and Constitutional Justice: European Union, an Ideal Without a Model - Safta, Marieta (Federalism as the Future of the Diverse EU?, 2025)
European Union as a state structure, it is important to examine the actions of the Court of Justice of the European Union and its collaboration, or lack thereof, with the Constitutional Courts of Member States. Although the Treaties of the EU may not explicitly include the constitutive element of self-determination, the internal actions of the Court of Justice of the European Union, along with the external actions of the Constitutional Courts, seem to be significantly filling this gap. This trend, characterised by an increase in the capacity of the courts (international and supranational) to shape the fragmented and explicitly or predominantly implicitly transferred state sovereignty, is assigned the role of the centripetal force of European integration. The research aims to analyse the integrative mechanism involving the ECJ and national courts, particularly CCs, with the intention of comprehending the intricacies of this collaborative mechanism, how it presents itself, the perspective of evolutions and the impact of constitutional justice on the future of the EU. Keywords: constitutional justice, European Union, constitutional courts, European Court of Justice, centripetal forces.